Роль свободных аминокислот в поддержании саногенного гомеостаза сердечно-сосудистой системы - Гараева, С.Н.; Постолати, Г.В.; Чокинэ, В.К. (Editura USM, 2024)
The article reviews the scientific literature on the impact of free amino acids on the healthogenicity of the cardiovascular system and against the development of many pathologies of the heart. It describes the influence of amino acids and amino acid groups on myocardial structure, metabolism, bioenergetics, myocardial bioenergetics, functionality.
Keywords: amino acids; healthogenicity; heart; cardiovascular system; metabolism; functionality